2020
DOI: 10.1002/ldr.3729
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen rhizodeposition by legumes and its fate in agroecosystems: A field study and literature review

Abstract: Quantification of legume nitrogen (N) rhizodeposition (N derived from roots) and its fate in agroecosystems is crucial for managing soil fertility, land productivity, and agriculture sustainability. In contrast to forage legumes, the N rhizodeposition by grain legumes is nearly unknown. Therefore, N rhizodeposition of four grain legumes and its transfer to subsequent wheat crops was quantified using the 15 N stem labeling method under field conditions. The N rhizodeposition of the grain legumes: peanut, soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…In addition, we found that PW increased the annual equivalent yield but decreased winter wheat yield in the first year. The introduction of legumes into the rotation system with cereals increased the subsequent cereal yields (Bundy et al, 1993; Preissel et al, 2015), which attributed to the N rhizodeposition from the legume (Wang et al, 2020b; Zang et al, 2018; Zhang et al, 2019). However, in our study, the available soil water before sowing is a key factor affecting the yield of winter wheat in the first year, due to a higher ET in the first summer season of PW, as soil water condition vastly affected the performance of winter wheat (Qin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that PW increased the annual equivalent yield but decreased winter wheat yield in the first year. The introduction of legumes into the rotation system with cereals increased the subsequent cereal yields (Bundy et al, 1993; Preissel et al, 2015), which attributed to the N rhizodeposition from the legume (Wang et al, 2020b; Zang et al, 2018; Zhang et al, 2019). However, in our study, the available soil water before sowing is a key factor affecting the yield of winter wheat in the first year, due to a higher ET in the first summer season of PW, as soil water condition vastly affected the performance of winter wheat (Qin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Considered as important regulators of ecosystem processes, the functional traits of plants influence soil characteristics, soil resources dynamic and the abundance and diversity of microorganisms [92,93]. The differences observed between legumes and cereals are related to particular physiological functioning that allows them to fix atmospheric N 2 , to have N-rich tissues and to enrich the soil in N such as those reported in the literature [20,94,95]. For example, ACP activity in the soil is produced and released by both roots and microorganisms.…”
Section: Variability Of Enzymatic Activities According To Plant Cover Cropsmentioning
confidence: 99%
“…In the same pot experiment, we observed that microplastics inhibited the growth of wheat (Zang et al, 2020). In turn, it could reduce rhizodeposition and as a consequence reduce the production of microbial enzymes due to a lack of energy resources (Wang et al, 2020; Zang et al, 2019). In line with this, PVC addition suppressed C‐degrading enzymes, whilst 1% and 20% of PE addition decreased N‐degrading enzymes, compared to the soil without microplastics ( p < 0.05, Figure 4).…”
Section: Discussionmentioning
confidence: 99%